Prevalence of dyslipidemia, atherogenic and cardiovascular risk in overweight and obese adolescents - Clara dos Santos de Andrades; Victória Volkweis Poletti; Vera Elizabeth Closs; Andreia da Silva Gustavo; Margareth da Silva Oliveira; Márcio Vinícius Fagundes Donadio; Ana Maria Pandolfo Feoli (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To analyze the lipid profile and cardiovascular risk of overweight and obese adolescents and correlate the findings with anthropometric measurements. Methods: This is a cross-sectional study on overweight and obese adolescents of both sexes (aged 14 to 18 years old). The collected variables were sex, weight, height, age, total cholesterol, triglycerides, High-density lipoprotein (HDL) and low-density lipoprotein (LDL). The Atherogenic Index of Plasma and Castelli Risk Indices I and II were calculated. These indices were classified into cutoff points to stratify cardiovascular risk. The anthropometric profile was evaluated by Z score according to Body Mass Index for age. Significance level was considered as p≤0.05. Results: A total of 146 adolescents participated in the study; the mean age was 16.4±1.1 years and most of them were girls (74.7%) and obese (52.7%). The prevalent dyslipidemias were high triglycerides (47.9%), LDL (26.7%), total cholesterol (37.7%), and low HDL (46.6%). Most adolescents presented increased atherogenic risk according to the Atherogenic Index of Plasma (55.5%); 15.1% presented high cardiovascular risk according to Castelli Risk Index I; and 13.7%, according to Castelli Risk Index II. Boys presented higher values of anthropometric measurements and Castelli Risk Indices I and II in relation to girls - who, conversely, presented higher values of HDL. There was a positive correlation of the Z score with Atherogenic Index of Plasma and a negative correlation with HDL. Conclusions: The adolescents of the study presented high prevalence of cardiovascular and atherogenic risk according to the evaluated indices. In addition, the increased cardiovascular risk was correlated with higher Body Mass Index.